Fast Proton Exchange in Histidine: Measurement of Rate Constants through Indirect Detection by NMR Spectroscopy. Issue 21 (9th April 2014) - Sehgal, Akansha Ashvani; Duma, Luminita; Bodenhausen, Geoffrey; Pelupessy, Philippe
Abstract Owing to its imidazole side chain, histidine participates in various processes such as enzyme catalysis, pH regulation, metal binding, and phosphorylation. The determination of exchange rates of labile protons for such a system is important for understanding its functions. However, these rates are too fast to be measured directly in an aqueous solution by using NMR spectroscopy. We have obtained the exchange rates of the NH3+ amino protons and the labile NHε2 and NHδ1 protons of the imidazole ring by indirect detection through nitrogen‐15 as a function of temperature (272 K<T<293 K) and pH (1.3<pH<4.9) of uniformly nitrogen‐15‐ and carbon‐13‐labeled L‐histidine⋅HCl⋅H2O. Exchange rates up to 8.5×104 s−1 could be determined (i.e., lifetimes as short as 12 μs). The three chemical shifts δHi of the invisible exchanging protons Hi and the three one‐bond scalar coupling constants 1J(N, Hi) could also be determined accurately.